Turkish version of the Yale Food Addiction Scale: preliminary results of factorial structure, reliability, and construct validity - Zehra Buyuktuncer; Aslı Akyol; Aylin Ayaz; Reyhan Nergiz-Unal; Burcu Aksoy; Erdal Cosgun; Pınar Ozdemir; Gulden Pekcan; Halit Tanju Besler (BMC, 2019)
Abstract Background Yale Food Addiction Scale (YFAS) was established to identify individuals exhibiting signs of addiction towards certain types of food. This study aimed to develop a Turkish version of the Yale Food Addiction Scale and test its psychometric properties. Methods The backward translation techniques were used to develop Turkish versions of the YFAS, and its reproducibility was assessed. Turkish version of the YFAS was administered to a total of 1033 participants (439 men and 594 women), aged 19-65 years. Exploratory factor analysis and confirmatory factor analysis were used to examine the factorial structure of the tool. Construct validity was assessed by principal component factor analysis with varimax rotation. Reliabilities were estimated with Cronbach's alpha coefficient. The criterion-related validity was tested by the administration of Eating Attitude Test-26 (EAT-26) to all participants. Results The primary factor loadings for seven items were ranged between 0.45 and 0.79, and no items cross-loaded onto other factors. The fit indices showed that eight items of the YFAS were a good representation of the item responses and each item loaded significantly on the specified factor (p < 0.001 for each). YFAS subscales had a high internal consistency and test-retest reliability. The criterion-related validity of the tool showed a positive relationship with scales of the EAT-26. Conclusion Current study suggested that the Turkish version of the YFAS is a reliable, valid, and useful tool for assessing the signs of food addiction in a non-clinical sample.